2006
DOI: 10.1302/0301-620x.88b12.17696
|View full text |Cite
|
Sign up to set email alerts
|

Delayed ruptures of the extensor tendon secondary to the use of volar locking compression plates for distal radial fractures

Abstract: The use of volar locking compression plates for the treatment of fractures of the distal radius is becoming increasingly popular because of the stable biomechanical construct, less soft-tissue disturbance and early mobilisation of the wrist. A few studies have reported complications such as rupture of flexor tendons. We describe three cases of rupture of extensor tendons after the use of volar locking compression plates. We recommend extreme care when drilling and placing the distal radial screws to prevent da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
116
1
22

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 174 publications
(147 citation statements)
references
References 20 publications
(15 reference statements)
1
116
1
22
Order By: Relevance
“…Although volar plates are usually well tolerated, they can lead to impingement on the extensor tendons when the fixation screws are too long and extend beyond the dorsal cortex of the radius. This form of impingement has been reported in several articles in the orthopedics literature [8][9][10][11][12], but we are unaware of similar studies in the radiology literature.…”
Section: Sonography Of Screw Impingement On Extensor Tendons After Vomentioning
confidence: 67%
See 1 more Smart Citation
“…Although volar plates are usually well tolerated, they can lead to impingement on the extensor tendons when the fixation screws are too long and extend beyond the dorsal cortex of the radius. This form of impingement has been reported in several articles in the orthopedics literature [8][9][10][11][12], but we are unaware of similar studies in the radiology literature.…”
Section: Sonography Of Screw Impingement On Extensor Tendons After Vomentioning
confidence: 67%
“…All were treated with Kirschner-wire fixation and not with volar plating [8]. Although the authors of several articles in the orthopedics literature have described extensor tendon tears caused by protruding screws [9][10][11][12], in none was sonography used preoperatively.…”
Section: Sonography Of Screw Impingement On Extensor Tendons After Vomentioning
confidence: 99%
“…Al-Rashid et al [31] reported an incidence of extensor tendon rupture of 8.6 % of 35 cases (three cases) treated with an AO volar locking plate, citing screw penetration of the dorsal cortex and careless drilling technique as principle causes. Other authors reporting extensor tendon irritation and ruptures have cited similar reasons [32][33][34][35].…”
Section: Discussionmentioning
confidence: 99%
“…1 This technique can, however, be responsible for complications such as tendon rupture that are caused by screws passing through the dorsal cortex of the distal radius. [2][3][4] A tangential X-ray view of the dorsal distal radius, or "skyline" view, has been described to detect the screws that are too long. 5 The accuracy of this view has been validated by experimental studies.…”
mentioning
confidence: 99%